Turath - heritage - Denan, Zuraini (s.n, 2012)
This is a book project illustrating the documentation of the heritage studies course. The book is a compilation of the fieldwork data of heritage studies 2011 course. Among the heritage buildings documented were Sultan Abdullah Masjid, Pekan, Pahang, Lal Bargh Fort, Dhaka, Bangladesh, Sunan Giri Masjid, Gersik, Surabaya and Sunan Ampel Masjid, Surabaya and Haghighi House, Esfahan, Iran. The focus of the manuscript is to showcase the significance heritage buildings and the local culture of different ethnic groups of Muslims. It explains how Islam was practiced and how the buildings were used by Muslims of different culture. The data were mainly documented in illustrations (sketches, drawings and photographs) format, to publish similar to coffee table book format